Struktur Cerpen “Yuki no Hi” Karya Higuchi Ichiyō - Zaki Ainul Fadli; Dewi Kusmiati (Diponegoro University, 2021)
Short stories are one type of modern literary work that has the privilege of forming a whole short story but still interesting for readers. The whole story in the short story cannot be separated from the elements that make it up. This study aimed to determine the intrinsic elements of the short story Yuki no Hi by Higuchi Ichiyō. The elements analyzed were themes and messages, characters and characterizations, plot, setting, and point of view. The theory used is the theory of structuralism with literature review techniques and qualitative analysis techniques. This research shows that the structure of this short story forms a unity of an exciting story from beginning to the end because of the integration of intrinsic elements in supporting the story presented. In addition, the use of deautomation techniques that delay the reader's understanding until the end of the story has succeeded in making the suspense of the story more interesting